Effecting product reliability and life cycle costs with early design phase product architecture decisions. (14th January 2008) - Salonen, Mikko; Holtta-Otto, Katja; Otto, Kevin
Identifying the impact of a design decision on a product's life cycle characteristics is important, but often difficult. Constructing links between these aspects is even more challenging in the early phases of design, since the consequences of the decisions are far away and little is yet known about the product's life cycle. Nevertheless, early design decisions have a high influence on the life cycle characteristics of a product. One early design decision is the selection of product architecture, that is, the fundamental structure and layout of a product. In this paper, we present a method to determine a relative comparison of product architectures based on a model of life cycle costs that can be assessed very early in the design process. The method utilises reliability distributions, relative cost estimates and cost incurrence distributions. We demonstrate our method on a real industrial case study of an energy-producing device. The alternative product architectures of the product are identified to possess very different life cycle characteristics. The relative comparison considers these characteristics and provides valuable information to support the design decision.